(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Jumping ability is one of the key components of successful performance in modern volleyball, as a significant part of gameplay actions (attacks, blocking, serves) depends on an athlete’s ability to execute high and explosive jumps. The increasing intensity of the game and growing physical demands on players necessitate the improvement of training methodologies for developing jumping abilities. Recent studies indicate that traditional methods do not always consider the individual characteristics of athletes, their physical fitness levels, coordination abilities, and the specificity of training loads. This study highlights the need for a comprehensive approach to developing jumping ability, combining plyometric, strength, and coordination exercises. Special attention is given to the interrelation of jumping characteristics with such parameters as agility, reaction speed, and balance. The research also examines the effectiveness of various testing methodologies for jumping ability and their role in adjusting training programs. The proposed practical recommendations on using specialized exercises and test tasks allow for improving the efficiency of the training process, reducing the risk of injuries, and enhancing the players’ overall performance. The established test standards can be utilized to assess the training levels of athletes across different age groups. Considering the general principles of developing jumping abilities, achieving an optimal training effect requires: gradually increasing the intensity and volume of exercises; applying a comprehensive approach, including strength, coordination, and plyometric training; using variability in training – incorporating different methods and exercises helps prevent muscle adaptation to monotonous loads; implementing an individual approach – the training program should take into account the athlete’s fitness level, biomechanical characteristics, and playing position on the volleyball court. Future research should focus on developing personalized training programs for players in different positions, as well as evaluating the long-term impact of various training approaches on the jumping abilities of volleyball players.